Report on a Rare Case of Limited CD4/CD8 Double-Positive Paget Reticulosis with Literature Review - Zhang Y; Zhang M; Li Y; Wang H (Clinical, Cosmetic and Investigational Dermatology, 2024)
Yunfang Zhang,1,* Ming Zhang,2,* Yuan Li,3 Huaji Wang3 1The Department of Oncology, Hainan Provincial Hospital of TCM, Haikou, Hainan, People’s Republic of China; 2Department of Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China; 3Department of Cosmetic Dermatology, The Fifth People’s Hospital of Hainan Province, Haikou, Hainan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huaji Wang; Yuan Li, Department of Cosmetic Dermatology, The Fifth People’s Hospital of Hainan Province, No. 8 Longhua Road, Longhua District, Haikou, Hainan, 570100, People’s Republic of China, Email 13876838737@163.com; liyuanskin@hotmail.comAbstract: Restricted pagetoid reticulosis, also known as Woringer-Kolopp disease, represents a rare cutaneous lymphoproliferative disorder categorized as an isolated variant of mycosis fungoides. This report presents a case involving limited pagetoid reticulosis affecting the right upper extremity in a 25-year-old female. The patient had been experiencing plaques on the right upper extremity for a decade. Dermatologic examination revealed well-defined scaly plaques on the right forearm, surrounded by hyperpigmented patches. Skin histopathology demonstrated atypical mononuclear cell infiltration in the lower part of the epidermis, forming nests. Immunohistochemistry indicated CD3+, CD4+, CD5+, CD7+, CD8+, CD30+, and Ki-67-positive staining. Additionally, CD20, CD79α, and PD-1 were negative. Monoclonal rearrangement of T-cells was identified in TCR β and TCR γ through clonality assessment. The diagnosis of limited paget-like reticulocyte hyperplasia was established, leading to surgical resection. A review of the literature affirmed the variable immunophenotype of pagetoid reticulosis, with atypical cells exhibiting four types: (1) CD3+, CD4+, CD8+-type; (2) CD3+, CD4-, CD8+-type; (3) CD3+, CD4-, CD8-type; and (4) CD3+, CD4+, CD8+-type—relatively uncommon in the restrictive type. This case report details the clinical features, histologic and morphologic characteristics, immunohistochemical phenotype, diagnosis, and differential diagnosis of a rare CD3+, CD4+, CD8+ limited pagetoid reticulosis. The lesion was surgically resected, and the patient underwent a 3-year follow-up to observe its prognosis.Keywords: pagetoid reticulosis, restricted type, tunica granulosa, CD4+, CD8+